Solid material containing Li, Mg, P, S and halogen elements

JP2025500242APending Publication Date: 2025-01-09SPECIAL OPERATIONS FRENCH CO
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
JP2024535859
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-17
Filing Date
2022-12-14
Publication Date
2025-01-09

Smart Images

  • Figure 2025500242000001
    Figure 2025500242000001
  • Figure 2025500242000002
    Figure 2025500242000002
  • Figure 2025500242000003
    Figure 2025500242000003
Patent Text Reader

Abstract

The present invention relates to a compound having the following general formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, (y is a number such as 1.3≦y≦1.6) The present disclosure also relates to the use of this solid material as a solid electrolyte, in particular for electrochemical devices such as batteries.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to European Patent Application No. 21306820.8, filed December 17, 2021, the entire contents of which are incorporated herein by reference for all purposes.

[0002] The present invention relates to a solid material according to the following general formula (I) and a method for producing said solid material: Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, (y is a number such as 1.3≦y≦1.6)

[0003] The present disclosure also refers to the use of this solid material as a solid electrolyte, especially for electrochemical devices such as batteries. [Background technology]

[0004] Lithium batteries are used to power portable electronic devices and electric vehicles due to their high energy and power density. Conventional lithium batteries utilize a liquid electrolyte consisting of lithium salts dissolved in an organic solvent. The above-mentioned system has safety issues since the organic solvent is flammable. If lithium dendrites form and pass through the liquid electrolyte medium, they can cause short circuits and generate heat, which can ultimately result in accidents leading to serious injuries. Since the electrolyte solution is a flammable liquid, there are concerns about leakage, fire, etc., when used in batteries. In light of such concerns, it is expected that a safer solid electrolyte will be developed as the electrolyte for next-generation lithium batteries.

[0005] Non-flammable inorganic solid electrolytes present solutions to safety issues. Furthermore, their mechanical stability helps suppress lithium dendrite formation, prevent self-discharge and heating problems, and extend the battery life.

[0006] Solid sulfide electrolytes are advantageous for lithium battery applications due to their high ionic conductivity and mechanical properties. These electrolytes can be pelletized and attached to electrode materials by cold pressing, thereby eliminating the need for high-temperature assembly processes. Eliminating the high-temperature sintering process removes one of the challenges associated with using lithium metal anodes in lithium batteries. There is an increasing demand for solid-state electrolytes with high conductivity for lithium ions to widely popularize and use all-solid-state lithium batteries. An important class of such solid electrolytes is materials with the composition Li6PS5X (X = Cl, Br) having an argyrodite structure. Sulfide-based solid electrolytes such as Li6PS5X (X = Cl, Br, I) with an argyrodite crystal structure are superionic conductors with high electrochemical stability and ionic conductivity. Due to these interesting properties, such materials have been the subject of much research, some of which involve the use of dopants. U.S. Patent Application Publication No. 2021 / 047195 describes the use of thioophilic metals such as Mn, Fe, Co, Ni, Cu, Zn, Hg, and Mo to modify the argyrodite structure and prevent the formation of H2S, thereby stabilizing the material.

[0007] U.S. Patent Application Publication No. 2020 / 0194827 describes a sulfide-based solid electrolyte doped with alkaline earth metals to improve ionic conductivity and a method for manufacturing the same. The sulfide-based solid electrolyte represented by the formula Li 6-2x Me x PS5Ha (where Me is an alkaline earth rare earth element, Ha is a halogen element, and 0 < x ≦ 0.5) exhibits higher ionic conductivity than the undoped argyrodite of the formula Li6PS5Cl. However, the increase in ionic conductivity is quite limited.

[0008] International Publication No. 2021117869 pamphlet describes a sulfide-based solid electrolyte doped with a plurality of metals and a method for producing the same in order to improve moisture resistance and reduce the generation of H2S while maintaining its ionic conductivity. The sulfide-based solid electrolyte has the formula Li a M b PS c X d wherein 3.0 ≦ a ≦ 6.5, 0 < b ≦ 2.0, 3.5 ≦ c ≦ 5.5, and 0.5 ≦ d ≦ 3.0, X is a halogen, and M may be Mg. However, the measured ionic conductivity is also quite limited in the exemplified Mg-containing sulfides.

[0009] However, there is a need for new solid sulfide electrolytes with optimized performance such as higher ionic conductivity and lower activation energy without sacrificing other important properties such as chemical and mechanical stability.

Summary of the Invention

[0010] Surprisingly, as detailed below, the new solid sulfide electrolyte LiMgPSX with a clearly defined composition has been found to have high ionic conductivity and low activation energy compared to i) the normal Li6PS5Cl material and ii) the LiMgPSX solid materials disclosed in the prior art. The LiMgPSX solid materials of the present invention exhibit at least the same chemical and mechanical stability and processability as their conventional lithium argyrodites. The solid materials of the present invention can also be manufactured with improved productivity and enable control of the form of the resulting product.

[0011] The present invention relates to a solid material according to the following general formula (I). Li 7-2x-y Mg x PS 6-y X y (I) (wherein, ·X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof, x is a number such as 0.01≦x≦0.35, y is a number such as 1.3≦y≦1.6.

[0012] The present invention also relates to a compound represented by the following general formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, y is a number such as 1.3≦y≦1.6. The present invention also relates to a process for producing a solid material according to the present invention, the process comprising the steps of: a) combining ingredients, optionally in one or more solvents, to obtain a composition; b) optionally subjecting the composition obtained in step a) above to a mechanical treatment; c) optionally removing at least a portion of the one or more solvents from the composition obtained in step b) above to obtain a solid residue; d) optionally pressing said solid residue from step c) into pellets; e) heating the residue obtained in step c), for example in the form of pellets, at a temperature in the range of 350° C. to 580° C. for a time in the range of 1 hour to 12 hours, thereby forming the solid material; f) optionally processing said solid material obtained in step e) to a desired particle size distribution; Includes.

[0013] The present invention also relates to a compound represented by the following general formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, y is a number such as 1.3≦y≦1.6. The present invention also relates to a process for producing a solid material according to the present invention, a') mixing the raw material with one or more solvents to obtain a solution; b') removing at least a portion of the one or more solvents from the composition obtained in step a') to obtain a solid residue; c') optionally pressing the solid residue from step b') above into pellets; d') optionally heating said residue obtained in step b'), for example in the form of pellets, under an inert atmosphere to a temperature in the range of 350°C to 580°C for a time in the range of 1 hour to 12 hours, thereby forming said solid material; e') optionally processing the solid material obtained in step d') to a desired particle size distribution; Includes.

[0014] The invention further relates to the solid materials obtainable by the process.

[0015] The present invention relates to a compound represented by the following formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, y is a number such as 1.3≦y≦1.6. The present invention also relates to the use of the solid material as a solid electrolyte.

[0016] The present invention relates to a compound represented by the following formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, (y is a number such as 1.3≦y≦1.6) The present invention also relates to a solid electrolyte comprising at least one of the solid materials.

[0017] The present invention relates to a compound represented by the following formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, (y is a number such as 1.3≦y≦1.6) The present invention also relates to an electrochemical device comprising at least one solid electrolyte comprising at least one of the solid materials described above.

[0018] The present invention relates to a compound represented by the following formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, (y is a number such as 1.3≦y≦1.6) The present invention also relates to a solid-state battery comprising at least one solid electrolyte comprising at least one of the solid materials described above.

[0019] The present invention relates to a compound represented by the following formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, (y is a number such as 1.3≦y≦1.6) The present invention also relates to a vehicle comprising at least one solid-state battery comprising at least one solid electrolyte comprising at least one of the solid-state materials.

[0020] The present invention also provides A metal substrate; at least one layer directly adhered to the metal substrate, (i) Formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, y is a number such as 1.3≦y≦1.6. of solid materials, (ii) at least one electroactive compound (EAC); (iii) optionally at least one lithium ion conducting material (LiCM) other than the solid-state material of the present invention; (iv) optionally, at least one electrically conductive material (ECM); (v) optionally, a lithium salt (LIS), and (vi) optionally at least one layer made from a composition comprising at least one polymeric binding material (P); The present invention also relates to an electrode comprising at least

[0021] The present invention relates to The following formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, y is a number such as 1.3≦y≦1.6. and Optionally, at least one polymeric binder material (P), optionally at least one metal salt, in particular a lithium salt, optionally at least one plasticizer; The present invention also relates to a separator comprising at least

[0022] definition Throughout this specification, unless the context requires otherwise, the terms "comprise" or "include" or variations such as "comprises", "comprising", "includes", "including" will be understood to mean the inclusion of a stated element or method step or group of elements or method steps, but not the exclusion of any other element or method step or group of elements or method steps. According to a preferred embodiment, the terms "comprise" and "comprising" and variations thereof mean "consisting only of". As used herein, the singular forms "a", "an" and "the" include plural aspects, unless the context clearly indicates otherwise. The term "and / or" includes the meaning "and", "or" and also all other possible combinations of elements associated with this term.

[0023] The term "to" should be understood to include the upper and lower limits. Ratios, concentrations, amounts, and other numerical data may be presented in a range format herein. It should be understood that such range formats are used merely for convenience and brevity and should be interpreted flexibly to include not only the numerical values ​​explicitly recited as the upper and lower limits of the range, but also to include all individual numerical values ​​or subranges contained within the range as if each numerical value and subrange were explicitly recited. For example, a temperature range of about 120°C to about 150°C should be interpreted to include not only the explicitly recited upper and lower limits of about 120°C to about 150°C, but also subranges such as 125°C to 145°C, 130°C to 150°C, and individual amounts such as decimal points within the specified range, for example, 122.2°C, 140.6°C, and 141.3°C.

[0024] The term "electrolyte" refers in particular to an electrolyte through which ions, such as Li + An electrolyte is a material that allows the movement of ions, e.g. Li, through it but does not conduct electrons. + The "solid electrolyte" of the present invention is particularly useful for conducting ions, such as Li, while electrically insulating the cathode and anode of a battery. + By "material" we mean any type of material that can move around within it.

[0025] As used herein, the term "argyrodite" or "argyrodite crystal" refers to a crystal structure or crystal bonding arrangement based on the crystal structure for the naturally occurring mineral argyrodite, a silver germanium sulfide mineral characterized by the chemical formula Ag8GeS6. Examples of this crystal structure also include the isomorphous argyrodite mineral, Ag8SnS6.

[0026] As used herein, the term "crystalline phase" refers to a fraction of a material that exhibits crystalline characteristics, for example, well-defined x-ray diffraction peaks as measured by x-ray diffraction (XRD).

[0027] As used herein, the term "peak" refers to a (2Θ) position on the x-axis of an XRD powder pattern of intensity v, in degrees (2Θ), that has a peak intensity substantially greater than background. In a set of XRD powder pattern peaks, the main peak is the peak of highest intensity that is associated with the compound or phase under analysis. The second main peak is the second most intense peak. The third main peak is the third most intense peak.

[0028] The term "electrochemical device" refers in particular to devices that generate and / or store electrical energy, for example by electrochemical and / or electrostatic processes. Electrochemical devices may include electrochemical cells, such as batteries, especially solid-state batteries. Batteries may be primary (i.e., for single or "disposable" use) or secondary (i.e., rechargeable) batteries.

[0029] As used herein, the terms "cathode" and "anode" refer to the electrodes of a battery. During a charge cycle in a Li secondary battery, Li ions leave the cathode and move through the electrolyte to the anode. During a charge cycle, electrons leave the cathode and move through an external circuit to the anode. During a discharge cycle in a Li secondary battery, Li ions move through the electrolyte and from the anode toward the cathode. During a discharge cycle, electrons leave the anode and move through an external circuit to the cathode.

[0030] The term "vehicle" or "vehicle" or other similar terms, as used herein, is understood to generally include motor vehicles such as passenger cars, including sport utility vehicles (SUVs), buses, trucks, various commercial vehicles, watercraft, including various boats and ships, aircraft, and includes hybrid vehicles, electric vehicles, plug-in hybrid electric vehicles, hydrogen vehicles, and other alternative fuel vehicles (e.g., fuels derived from sources other than petroleum). As referred to herein, a hybrid vehicle is a vehicle that has two or more different power sources, such as a vehicle that is powered by gasoline and electric power. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] First, the present invention relates to a compound represented by the general formula (I) Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, (y is a number such as 1.3≦y≦1.6) This relates to solid materials.

[0032] The solid material of the present invention is neutral in charge. It is understood that formula (I) is an empirical formula (gross formula) determined by elemental analysis. Therefore, formula (I) defines the composition averaged over all phases present in the solid material. X is preferably Cl.

[0033] Typically, 0.01≦x≦0.35, preferably 0.01≦x≦0.25, and in particular 0.01≦x≦0.2. Typically, 1.3≦y≦1.6, and in particular 1.3≦y≦1.5. In some embodiments, 0.01≦x≦0.25 and 1.3≦y≦1.5. In other embodiments, 0.01≦x≦0.2 and 1.3≦y≦1.5.

[0034] The solid material of the present invention may be an amorphous (glass) and / or crystallized (glass-ceramic) solid material. Only a part of the solid material may be crystallized. The crystallized part of the solid material may contain only one crystal structure or may contain several crystal structures. The crystallinity of the solid material (crystallinity of the crystal structure whose ionic conductivity is higher than that of the amorphous body) is preferably comprised between 80% and 100%. The solid material of the present invention preferably comprises a fraction consisting of crystalline phases, one of said crystalline phases having an argyrodite structure. Preferably, said crystalline phase having an argyrodite phase constitutes between 90% and 100% of the total weight of the fraction consisting of crystalline phases. Such a fraction may be determined by X-ray diffraction using Rietveld refinement of the total diffractogram. This refinement can be performed in the FullProf software by using the multi-step refinement option.

[0035] The solid material of the present invention has the structural unit PS4 3- and structural unit PO4 3- and preferably comprises the structural unit PS4 3- The amount and structural unit of PO4 3- The ratio between the amount of is in the range of 1000:1 to 9:1.

[0036] The solid material of the present invention may include peaks at least at 15.65°±0.5°, 25.53°±0.5°, 30.16°±0.5°, and 31.52°±0.5° (2θ) when analyzed by X-ray diffraction using CuKα radiation at 25° C. The crystallographic space group of the solid material of the present invention is preferably space group 226 (F43m). In this space group, the lattice parameters of the solid material of the present invention may be in the range of 9,680 Å to 9,860 Å, as measured by X-ray diffraction using CuKα radiation at 25° C. and further calculated by dedicated software such as Fullprof software using improved methods such as the Rietveld method and Le Bail method.

[0037] In some embodiments, the solid material of formula (I) according to the present invention may be:

[0038] [Table 1]

[0039] [Table 2]

[0040] [Table 3]

[0041] The composition of the compound of formula (I) can be determined by chemical analysis using techniques well known to those skilled in the art, such as, inter alia, X-ray diffraction (XRD) and inductively coupled plasma-mass spectrometry (IPC-MS). The solid material of the present invention may be in the form of a powder. The powder can be characterized by its size or particle size distribution (PSD). The particle size of the powder, as measured by laser diffraction in p-xylene, is: a d50 value of less than 50 μm, for example less than 40 μm, less than 30 μm or less than 20 μm, A d10 value of more than 0.05 μm, and / or a d90 value of less than 100 μm, for example less than 90 μm, less than 80 μm or less than 70 μm, It may also be one that indicates:

[0042] The powder may be composed of agglomerated particles.

[0043] Particle size distribution (PSD), e.g. d50, d10 and d90 values, may be measured for a large number of particles (at least 150) using a scanning electron microscope (SEM). Alternatively, measurements may be performed by laser diffraction in p-xylene. The d50 value has the usual meaning used in the field of particle size distribution. The dn value corresponds to the diameter of a particle where n% of the particles have a diameter less than dn. The d50 (median) is defined as the size value corresponding to the cumulative distribution at 50%. These parameters are usually determined from the volumetric distribution of diameters of a dispersion of particles of a solid material in a solution, obtained with a laser diffractometer, using standard procedures predefined by the instrument's built-in software. The laser diffractometer uses the technique of laser diffraction to measure particle size by measuring the intensity of light scattered when a laser beam passes through a dispersed particulate sample. The laser diffractometer may be, for example, a Mastersizer 3000 manufactured by Malvern.

[0044] D50 may be measured, inter alia, after treatment under ultrasound, which may include inserting an ultrasonic probe into a dispersion of a solid material in a solution and subjecting the dispersion to ultrasonic treatment.

[0045] The particles of the powder may be spherical in shape.

[0046] The particles of the powder may exhibit a sphericity SR of 0.8 to 1.0, more specifically 0.85 to 1.0, and even more specifically 0.90 to 1.0. SR may preferably be 0.90 to 1.0 or 0.95 to 1.0. The sphericity of a particle is calculated from the measured circumference P and the projected area A of the particle using the following formula: SR=4πA / P 2 .

[0047] For an ideal sphere, SR is 1.0, and for spherical particles, SR is less than 1.0. SR may be determined by dynamic image analysis (DIA). Examples of devices that can be used to perform DIA are Retsch's CAMSIZER® P4 or Sympatec's QicPic®. More specifically, sphericity can be measured according to ISO 13322-2 (2006). DIA generally requires the analysis of a statistically meaningful large number of particles (e.g., at least 500 or even at least 1000).

[0048] The powders of the present invention are also characterized by low release of H2S under certain conditions, which can be measured by exposing the powder to a moist atmosphere and measuring the amount of H2S released during the first 50 minutes that the powder is in contact with the atmosphere.

[0049] The solid material may advantageously exhibit an ionic conductivity of at least 3.3 mS / cm, such as at least 3.4 mS / cm, such as from 3.5 to 15.0 mS / cm, or from 3.8 to 10.0 mS / cm, as measured on a pressed (500 MPa) pellet by impedance spectroscopy.

[0050] The ionic conductivity measurements are carried out on pressed pellets. Typically, pressed pellets are produced using uniaxial or isostatic pressure. When applying uniaxial pressure to form pellets, a pressure of more than 100 MPa, advantageously more than 300 MPa, is applied for a duration of at least 30 seconds. Measurements are typically carried out under uniaxial pressures of 2 MPa to 200 MPa.

[0051] The present invention also refers to a method for producing a solid material according to general formula (I), comprising at least the step of bringing at least lithium sulfide, phosphorus sulfide, a halogen compound and a magnesium compound, optionally in one or more solvents. One or more of lithium sulfide, phosphorus sulfide, a halogen compound and a magnesium compound may be used.

[0052] In particular, the present invention also relates to a method for producing a solid material according to general formula (I), comprising at least the step of reacting, optionally in one or more solvents, at least lithium sulfide, phosphorus sulfide, a halogen compound and a magnesium compound. One or more of lithium sulfide, phosphorus sulfide, a halogen compound and a magnesium compound may be used.

[0053] The solid materials of the present invention may be produced by any method known in the prior art for producing sulfide-based glass solid electrolytes, such as, for example, a melt extrusion method, a full solution method, a mechanical milling method, or a slurry method in which the raw materials are reacted (optionally in one or more solvents).

[0054] The present invention also relates to a process for the manufacture of a solid material according to general formula (I), comprising the steps of: a) combining ingredients, optionally in one or more solvents, to obtain a composition; b) optionally subjecting the composition obtained in step a) to a mechanical treatment; c) optionally removing at least a portion of the one or more solvents from the composition obtained in step b) to obtain a solid residue; d) optionally pressing said solid residue from step c) into pellets; e) heating the residue obtained in step c), for example in the form of pellets, to a temperature in the range of 350° C. to 580° C. for a time in the range of 1 hour to 12 hours under an inert atmosphere, thereby forming the solid material; f) optionally processing said solid material obtained in step e) to a desired particle size distribution; The process includes:

[0055] In some embodiments, step a) is carried out under an inert atmosphere. The inert atmosphere used in step a) refers to the use of an inert gas, i.e., a gas that does not undergo adverse chemical reactions under the conditions of the reaction. Inert gases are generally used to avoid undesirable chemical reactions, such as oxidation and hydrolysis reactions with oxygen and moisture in the air. Thus, an inert gas refers to a gas that does not react chemically with other reagents present in a particular chemical reaction. In the context of this disclosure, the term "inert gas" refers to a gas that does not react with the solid material precursor. Examples of "inert gases" include, but are not limited to, nitrogen, helium, argon, carbon dioxide, neon, xenon, H2S, O2, with less than 1000 ppm of water in liquid and suspended form (including condensed). The gas can also be pressurized.

[0056] It is preferable that the raw materials are stirred when they are contacted with each other under an atmosphere of an inert gas such as nitrogen or argon. The dew point of the inert gas is preferably −20° C. or lower, particularly preferably −40° C. or lower. The pressure may be 0.0001 Pa to 100 MPa, preferably 0.001 Pa to 20 MPa, preferably 0.01 Pa to 0.5 MPa.

[0057] Preferably in step a), the inert atmosphere comprises an inert gas such as H2S, dry N2, dry argon or dry air (dry may refer to a gas having less than 800 ppm water in liquid and suspended form, including condensed). The composition ratio of each element can be controlled by adjusting the amount of raw material compounds when the solid material is produced. The raw materials and their molar ratios are selected according to the target stoichiometry. The target stoichiometry defines the ratio between the elements Li, Mg, P, S and X that can be obtained from the applied amount of precursor under the condition of complete conversion without side reactions and other losses.

[0058] Lithium sulfide refers to a compound that contains one or more sulfur atoms and one or more lithium atoms, or alternatively, one or more sulfur-containing ionic groups and one or more lithium-containing ionic groups. In certain preferred embodiments, the lithium sulfide may be composed of sulfur atoms and lithium atoms. Preferably, the lithium sulfide is Li2S.

[0059] Phosphorus sulfide refers to a compound that contains one or more sulfur atoms and one or more phosphorus atoms, or one or more sulfur-containing ionic groups and one or more phosphorus-containing ionic groups. In certain preferred embodiments, the phosphorus sulfide may be composed of sulfur and phosphorus atoms. Non-limiting exemplary phosphorus sulfides include P2S5, P4S3, P4S 10 , P4S4, P4S5, P4S6, P4S7, P4S8 and P4S9.

[0060] A halogen compound refers to a compound that contains one or more halogen atoms, such as F, Cl, Br, or I, through a chemical bond (e.g., ionic or covalent bond) to other atoms that constitute the compound. In certain preferred embodiments, the halogen compound contains one or more of F, Cl, Br, I, or a combination thereof, and one or more metal atoms. In another preferred embodiment, the halogen compound contains one or more of F, Cl, Br, I, or a combination thereof, and one or more non-metal atoms. Non-limiting examples include metal halides, such as LiF, LiBr, LiCl, LiI, NaF, NaBr, NaCl, NaI, KaF, KBr, KCl, and KI. In certain preferred embodiments, the halogen compound suitable for use in the solid electrolyte of the all-solid-state Li-ion battery may contain one or more halogen atoms and Li. Preferably, the halogen compound may be selected from the group consisting of lithium bromide (LiBr), lithium chloride (LiCl), lithium iodide (LiI), and combinations thereof.

[0061] The magnesium compound refers to a compound that contains one or more Mg atoms through chemical bonds (e.g., ionic or covalent bonds) with other atoms that constitute the compound. In another embodiment, the magnesium compound may be metallic magnesium. In a particular preferred embodiment, the magnesium compound may contain one or more Mg atoms and one or more non-metallic atoms, such as S, Cl, or Br. The magnesium compound is preferably selected from MgS, MgCl2, and mixtures thereof. The magnesium compound of the present invention may also be a blend of metallic magnesium and elemental sulfur.

[0062] In some embodiments, the lithium sulfide is Li2S, the phosphorus sulfide is P2S5, the halogen compound is LiCl, and the magnesium compound is selected from MgS, MgCl2, and mixtures thereof.

[0063] Preferably, the solid material of the present invention is made using at least the following raw materials: Li2S, P2S5, LiCl, and a magnesium compound selected from MgS, MgCl2, and mixtures thereof. In some embodiments, the solid material of the present invention is made using the following raw materials: Li2S, P2S5, LiCl, and MgS. In some embodiments, the solid material of the present invention is made using the following raw materials: Li2S, P2S5, LiCl, and MgCl2.

[0064] Preferably, the lithium sulfide, phosphorus sulfide, halogen compound and magnesium compound are in the form of powder having an average particle size of 0.5 μm to 400 μm. The particle size can be evaluated by SEM image analysis or laser diffraction analysis.

[0065] The solvent may suitably be selected from one or more of polar or non-polar solvents capable of substantially dissolving at least one compound selected from lithium sulfide, phosphorus sulfide, halogen compounds and magnesium compounds, and may be one that substantially suspends, dissolves or otherwise miscible with the above components, such as lithium sulfide, phosphorus sulfide, halogen compounds and magnesium compounds.

[0066] The solvent of the invention then constitutes in step a) the continuous phase in the dispersion of one or more of the abovementioned components. Depending on the components and the solvent, some of the components may be dissolved, partially dissolved or even in the form of a slurry (i.e., the components are not dissolved and thus form a slurry with the solvent).

[0067] In a particular preferred embodiment, the solvent is preferably a polar solvent, preferably selected from the group consisting of alkanols, particularly those having 1 to 6 carbon atoms, such as methanol, ethanol, propanol, and butanol, carbonates such as dimethyl carbonate, acetates such as ethyl acetate, ethers such as dimethyl ether, organic nitriles such as acetonitrile, aliphatic hydrocarbons such as hexane, pentane, 2-ethylhexane, heptane, decane, and cyclohexane, and aromatic hydrocarbons such as tetrahydrofuran, xylene, and toluene. Reference herein to a "solvent" is understood to include one or more mixed solvents.

[0068] The powder mixture may be mixed in an amount of about 1% by weight to 80% by weight based on the total weight of the powder mixture and the solvent, and the solvent may be mixed in an amount of about 20% by weight to 99% by weight. Preferably, the powder mixture may be mixed in an amount of about 25% by weight to 75% by weight based on the total weight of the powder mixture and the solvent, and the solvent may be mixed in an amount of about 25% by weight to 75% by weight. In particular, the powder mixture may be mixed in an amount of about 40% by weight to 60% by weight based on the total weight of the powder mixture and the solvent, and the solvent may be mixed in an amount of about 40% by weight to 60% by weight.

[0069] The temperature of step a) in the presence of a solvent is preferably between the melting temperature of the selected solvent and the boiling temperature of the selected solvent, at a temperature where no undesired reactivity between the solvent and the compound mixed with it is found. Preferably, step a) is carried out at temperatures between -20°C and 40°C, more preferably between 15°C and 40°C. In the absence of a solvent, step a) is carried out at temperatures between -20°C and 200°C, preferably between 15°C and 40°C.

[0070] The duration of step a) is preferably between 1 minute and 1 hour.

[0071] The mechanical treatment of the composition in step b) may be carried out by wet or dry milling, in particular by adding the powder mixture to a solvent and then milling at about 100 rpm to 1000 rpm, in particular for a duration of 10 minutes to 80 hours, more preferably about 4 hours to 40 hours.

[0072] Such milling is also known as reactive milling in the conventional synthesis of lithium argyrodite.

[0073] Mechanical milling has the advantage that the grinding occurs simultaneously with the formation of the glass mixture. Various methods can be used in mechanical milling, such as rotary ball mills, tumbling ball mills, vibratory ball mills, and planetary ball mills. Mechanical milling can be performed with or without balls such as ZrO2.

[0074] In such conditions, the lithium sulfide, phosphorus sulfide, a halogen compound and a magnesium compound are reacted (optionally in a solvent) for a period of time.

[0075] The temperature of step b) in the presence of a solvent is between the melting temperature of the selected solvent and the boiling temperature of the selected solvent, at a temperature where no undesired reactivity between the solvent and the compound is found. Preferably, step b) is carried out at a temperature between -20°C and 80°C, more preferably between 15°C and 40°C. In the absence of a solvent, step a) is carried out at a temperature between -20°C and 200°C, preferably between 15°C and 40°C.

[0076] The mechanical treatment of the composition in step b) can also be carried out using techniques well known in the art, such as by stirring, especially by using a standard powder mixer or a slurry mixer.

[0077] Typically, a paste or a blend of paste and liquid vehicle can be obtained at the end of step b).

[0078] In step c) at least a portion of the solvent is removed, particularly by means of removing at least about 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95% or 100% of the total weight of the solvent used, or any range included between these values. Solvent removal can be carried out by known methods used in the art, such as decantation, filtration, centrifugation, drying or a combination thereof.

[0079] The temperature in step c) is selected to allow the removal of the solvent, preferably when drying is selected as the method of solvent removal, the temperature is selected below the boiling temperature of the selected solvent and as a function of the partial vapor pressure of the selected solvent.

[0080] The duration of step c) is between 1 second and 100 hours, preferably between 1 hour and 20 hours. Such short durations can be obtained, for example, by using flash evaporation, such as by spray drying.

[0081] Step c) is preferably carried out under an atmosphere of an inert gas, such as nitrogen or argon. The dew point of the inert gas is preferably below -20°C, particularly preferably below -40°C. The pressure may be between 0.0001 Pa and 100 MPa, preferably between 0.001 Pa and 20 MPa, preferably between 0.01 Pa and 20 MPa. In particular, the pressure may be in the range of 0.0001 Pa to 0.001 Pa, in particular by using ultra-vacuum techniques. In particular, the pressure may be in the range of 0.01 Pa to 0.1 MPa, in particular by using primary vacuum techniques.

[0082] In step d), the solid residue from step c) can be pressed into pellets. For example, the solid residue can be pressed in a die to form pellets. The molding can be carried out in equipment known to those skilled in the art. For example, molding can be carried out using a uniaxial press or a simplex tablet press.

[0083] In step e), heating or heat treatment of the residue obtained in step c), for example in the form of pellets, can convert, inter alia, the above obtained amorphous powder mixture (glass) into a crystalline solid material or a mixture of glass and crystalline materials (glass-ceramics).

[0084] The heat treatment is carried out at a temperature ranging from 350°C to 580°C, for example from 370°C to 550°C or from 390°C to 530°C, in particular for a duration of 1 min to 12 h, preferably from 2 h to 10 h or from 3 h to 7 h. The heat treatment can start immediately at high temperature or by increasing the temperature at a rate comprised between 1°C / min and 20°C / min. The heat treatment can be completed by air quenching, or by natural cooling from the heating temperature, or by controlled lowering at a rate comprised between 1°C / min and 20°C / min.

[0085] Preferably, in step e), the inert atmosphere comprises an inert gas such as dry N2 or dry argon ("dry" may refer to a gas containing less than 800 ppm water in liquid and suspended form, including condensed). Preferably, in step e), the inert atmosphere is a protective gas atmosphere used to minimize, and preferably exclude, the access of oxygen and moisture.

[0086] The pressure during heating may be normal pressure or reduced pressure. The atmosphere may be an inert gas such as nitrogen and argon. The dew point of the inert gas is preferably -20°C or less, particularly preferably -40°C or less. The pressure may be 0.0001 Pa to 100 MPa, preferably 0.001 Pa to 20 MPa, preferably 0.01 Pa to 20 MPa. In particular, the pressure may be in the range of 0.0001 Pa to 0.001 Pa, in particular by using ultra-vacuum techniques. In particular, the pressure may be in the range of 0.01 Pa to 0.1 MPa by using primary vacuum techniques.

[0087] In step f), the solid material can be processed to the desired particle size distribution. If necessary, the solid material obtained by the process according to the invention as described above is ground (e.g. milled) into a powder. Preferably, the powder has a D50 value of the particle size distribution of less than 50 μm, more preferably less than 10 μm, even more preferably less than 5 μm, as measured by dynamic light scattering or image analysis.

[0088] Preferably, the powder has a particle size distribution D90 value of less than 100 μm, more preferably less than 10 μm, even more preferably less than 5 μm, as measured by dynamic light scattering or image analysis. In particular, the powder has a particle size distribution D90 value comprised between 1 μm and 100.

[0089] The present invention then relates to a process for the preparation of a solid material according to general formula (I), comprising: a') mixing the raw materials with one or more solvents under an inert atmosphere to obtain a solution; b') removing at least a portion of said one or more solvents from said composition as obtained in step a') to obtain a solid residue; c') optionally pressing the solid residue from step b') into pellets; d') optionally heating the solid residue obtained in step b') at a temperature in the range of 350°C to 580°C under an inert atmosphere, thereby forming a solid material; e') optionally processing the solid material obtained in step d') to a desired particle size distribution; It is also a process that includes

[0090] The various features of step a') are essentially the same as those of step a), e.g., with regard to precursors and solvents, etc. Preferably, the temperature in step a') is in the range of -200°C to 100°C, preferably -200°C to 10°C.

[0091] The characteristics of the removal of the solvent as described in step b') may be similar to those as indicated in step c).Preferably in step b') the temperature is in the range of 30°C to 200°C under an inert atmosphere and preferably under a pressure of 0.0001 Pa to 100 MPa.

[0092] In step c'), the solid residue from step b') can be pressed into pellets as represented in step d).

[0093] The heating of step d') can be carried out with the characteristics as indicated in step e), preferably at a temperature in the range of 350°C to 580°C under an inert atmosphere and preferably under a pressure of 0.0001 Pa to 100 MPa.

[0094] The characteristics of the processing of the solid material as described in step e') may be similar to those as indicated in step f).

[0095] The present invention also refers to a solid material of formula (I) as a solid electrolyte and to a solid electrolyte comprising at least a solid material of formula (I).

[0096] In this case, the solid electrolyte is at least a solid material of formula (I) and, optionally, at least one lithium ion conductive material (LiCM) other than the solid material of the present invention, such as lithium argyrodite, lithium thiophosphate such as glass or glass ceramics, Li3PS4, Li7PS 11 and lithium-filled garnet Li7La3Zr2O 12 Lithium conductive oxides (LLZO) such as (LLZO).

[0097] The solid electrolyte may also optionally include a polymer, such as styrene butadiene rubber, an organic or inorganic stabilizer, or dispersant, such as SiO2.

[0098] The present invention also relates to an electrochemical device comprising a solid electrolyte comprising at least the solid material of formula (I).

[0099] Preferably, in an electrochemical device, particularly a rechargeable electrochemical device, the solid electrolyte is a solid structural component for the electrochemical device selected from the group consisting of the cathode, the anode and the separator.

[0100] A further aspect of the present invention relates to a battery, more preferably an alkali metal battery, and in particular to a lithium battery comprising at least one, such as two or more, electrochemical devices of the present invention. The electrochemical devices can be combined with one another, for example in series or parallel connection, in the alkali metal battery of the present invention.

[0101] The present invention also relates to a solid-state battery comprising a solid electrolyte comprising at least the solid material of formula (I).

[0102] Typically, a lithium solid-state battery includes a positive electrode active material layer containing a positive electrode active material, a negative electrode active material layer containing a negative electrode active material, and a solid electrolyte layer formed between the positive electrode active material layer and the negative electrode active material layer, wherein at least one of the positive electrode active material layer, the negative electrode active material layer, and the solid electrolyte layer includes a solid electrolyte as defined above.

[0103] The cathode of an all-solid-state electrochemical device typically includes a solid electrolyte as an additional component in addition to the cathode active material, and the anode of an all-solid-state electrochemical device typically includes a solid electrolyte as an additional component in addition to the anode active material.

[0104] The morphology of the solid-state structure for an electrochemical device, in particular for an all-solid-state lithium battery, depends in particular on the morphology of the electrochemical device itself to be produced. The present invention further provides a solid-state structure for an electrochemical device, selected from the group consisting of a cathode, an anode and a separator, wherein the solid-state structure for an electrochemical device comprises a solid-state material according to the present invention.

[0105] Multiple electrochemical cells can be combined into an all-solid-state battery, having both solid electrodes and a solid electrolyte.

[0106] The solid-state materials disclosed above can be used to manufacture electrodes. The electrodes can be positive or negative electrodes.

[0107] The electrodes are typically A metal substrate; at least one layer directly adhered to the metal substrate, (i) Formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, · y is a number such that 1.3 ≤ y ≤ 1.6) of a solid material, (ii) at least one electroactive compound (EAC), (iii) optionally, at least one lithium ion conductive material (LiCM) other than the solid material of the present invention, (iv) optionally, at least one electrically conductive material (ECM), (v) optionally, a lithium salt (LIS), and (vi) optionally, at least one layer made from a composition comprising at least one polymer binding material (P), and comprising.

[0108] The numerical values x and y may belong to the ranges described above.

[0109] The electroactive compound (EAC) means a compound that can incorporate or insert lithium ions into its structure and release them during the charging and discharging stages of an electrochemical device. The EAC may be a compound that can intercalate and deintercalate lithium ions into its structure. For the positive electrode (cathode), the EAC may be a composite metal chalcogenide of the formula LiMeQ2 (wherein: · Me is at least one metal selected from the group consisting of Co, Ni, Fe, Mn, Cr, Al and V; · Q is a chalcogen such as O or S) and may be.

[0110] The EAC may more particularly be of the formula LiMeO2. Preferred examples of the EAC include LiCoO2, LiNiO2, LiMnO2, LiNi x Co 1-x O2 (0 < x < 1), LiNi x Co y Mn z O2 (0 < x, y, z < 1 and x + y + z = 1), for example LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2, LiNi 0.6 Mn 0.2 Co0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, Li(Ni x Co y Al z )O2(x+y+z=1) and spinel structured LiMn2O4 and Li(Ni 0.5 Mn 1.5 )O4 is one example. EAC is the formula M1M2(JO4) f E 1-f (In the formula, M1 is lithium, which may be partially replaced by another alkali metal, which represents less than 20% of M1; M2 is a transition metal with an oxidation level of +2 selected from Fe, Co, Mn, Ni or mixtures thereof, which may be partially replaced by one or more additional metals with oxidation levels of +1 to +5, inclusive, representing less than 35% of the M2 metal, JO4 is any oxyanion where J is P, S, V, Si, Nb, Mo or any combination thereof; E is a fluoride, hydroxide or chloride anion, f is generally the mole fraction of JO4 oxyanions in 0.75-1) The electroactive material may be a lithiated or partially lithiated transition metal oxyanion based material.

[0111] M1M2(JO4) as defined above f E 1-f The electroactive material is preferably phosphate-based. It may exhibit an ordered structure or a modified olivine structure.

[0112] For the positive electrode, the EAC may also be sulfur or Li2S.

[0113] For the positive electrode, the EAC may be a conversion type material such as FeS2, or FeF2, or FeF3.

[0114] For the negative electrode, the EAC may be selected from the group consisting of graphitic carbons capable of intercalating lithium. Further details regarding this type of EAC can be found in Carbon 2000, 38, 1031-1041. This type of EAC typically exists in the form of powder, flakes, fibers or spheres (e.g., mesocarbon microbeads).

[0115] EACs also include lithium metal; lithium alloy compositions (such as those described in U.S. Pat. No. 6,203,944 and WO 00 / 03444); generally, lithium alloys of the formula Li4Ti5O 12 These compounds generally contain mobile ions, i.e., Li + Lithium-silicon alloys, commonly known as lithium silicides with high Li / Si ratios, and in particular the formula Li 4.4 Lithium silicide of formula Si; and Li 4.4 It may also be a lithium-germanium alloy containing a crystalline phase of Ge. The EAC may also be a composite material based on silicon and / or silicon oxide-loaded carbonaceous materials, especially graphitic carbon / silicon and graphite / silicon oxide, where the graphitic carbon is composed of one or several carbons capable of intercalating lithium.

[0116] The ECM is typically selected from the group consisting of conductive carbonaceous materials and metal powders or fibers. The conductive carbonaceous materials may be selected from the group consisting of, for example, carbon black, carbon nanotubes, graphite, graphene, and graphite fibers, and combinations thereof. Examples of carbon black include ketjen black and acetylene black. Metal powders or fibers include nickel and aluminum powders or fibers.

[0117] The lithium salt (LIS) may be selected in the group consisting of LiPF6, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, LiB(C2O4)2, LiAsF6, LiClO4, LiBF4, LiAlO4, LiNO3, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO3CF3)2, LiC4F9SO3, LiCF3SO3, LiAlCl4, LiSbF6, LiF, LiBr, LiCl, LiOH and lithium 2-trifluoromethyl-4,5-dicyanoimidazole.

[0118] The function of the polymeric binder (P) is to bind the components of the composition. The polymeric binder is usually inert. It is preferably also chemically stable and facilitates electronic and ionic transport. Polymeric binders are well known in the art. Non-limiting examples of polymeric materials (P) include, inter alia: (1) VDF or TFE based polymers, especially in the form of copolymers, block copolymers or graft copolymers; (2) hydrogenated or non-hydrogenated diene based rubber polymers, especially in the form of block copolymers and graft polymers, such as polyisobutylene (PIB), styrene butadiene rubber (SBR), (hydrogenated) acrylonitrile butadiene rubber ((h)NBR), styrene-ethylene-butylene-styrene (SEBS); (3) polymethylmethacrylate (PMMA), polybutylacrylate (BA), styrene-butylacrylate (ST-BA), styrene methylacrylate (ST-MA), butylacrylate-acrylonitrile (BA-CN), etc. (4) polysaccharide-based polymers, copolymers, block copolymers and graft copolymers, such as carboxymethylcellulose (CMC), guar gum, etc.; (5) acrylonitrile-based polymers, especially in the form of copolymers, block copolymers and graft polymers, such as poly(acrylonitrile) (PAN), acrylonitrile-methylacrylate (PAN-MA), styrene-acrylonitrile (SAN), acrylonitrile-styrene-acrylate (ASA); (6) polyamide-imide (PAI) polymers, copolymers, block copolymers and graft polymers.

[0119] The polymeric material (P) can be selected from the list consisting of vinylidene fluoride (VDF) based (co)polymers. The polymeric material (P) can more particularly be a copolymer comprising or consisting of VDF and hexafluoropropylene (HFP) units.

[0120] The polymeric material (P) may be selected from the list consisting of styrene-based, optionally hydrogenated, thermoplastic elastomers, and may more particularly be butadiene-styrene rubber (SBR) or styrene-ethylene-butylene-styrene (SEBS).

[0121] The polymeric material (P) can be selected from the list consisting of polymers containing units of acrylonitrile. The polymeric material (P) can more particularly be a copolymer of acrylonitrile, butadiene and / or butyl acrylate.

[0122] The proportion of the solid material of the present invention in the composition may be 0.1% to 80% by weight, based on the total weight of the composition. In particular, this proportion may be 1.0% to 60% by weight, more particularly 5% to 30% by weight. The thickness of the electrode is not particularly limited and should be adjusted with respect to the energy and power required in the application. For example, the thickness of the electrode may be 0.01 mm to 1.000 mm.

[0123] The solid material of the present invention can also be used to manufacture a separator, which is an ion-permeable membrane placed between the anode and cathode of a battery. Its function is to allow the passage of lithium ions while blocking electrons and ensuring physical separation between the electrodes.

[0124] The separator of the present invention typically comprises at least The following formula (I): Li 7-2x-y Mg x P.S. 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or a combination thereof; x is a number such as 0.01≦x≦0.35, y is a number such as 1.3≦y≦1.6. and Optionally, at least one polymeric binder material (P), optionally at least one metal salt, in particular a lithium salt, optionally at least one plasticizer; Includes.

[0125] The numbers x and y can fall within the ranges mentioned above.

[0126] The electrodes and separators can be manufactured using methods well known to those skilled in the art, which typically involve mixing the components in a suitable solvent and removing the solvent. For example, the electrodes can be made using applying a slurry comprising the components of the composition and at least one solvent onto a metal substrate; the solvent is removed; The composition can be produced by a process including:

[0127] Common techniques known to those skilled in the art are: coating and calendaring, dry and wet extrusion, 3D printing, sintering of porous foams followed by impregnation. Common manufacturing techniques for electrodes and for separators are provided in Journal of Power Sources, 2018 382, ​​160-175. Other techniques may be used, such as extrusion, paste extrusion, (electrical) spraying, kneading followed by calendaring.

[0128] Electrochemical devices, particularly batteries such as the solid-state batteries described herein, can be used to manufacture or operate stationary applications such as automobiles, computers, personal digital assistants, cell phones, watches, camcorders, digital cameras, thermometers, calculators, laptop BIOS, communication equipment or remote car locks, and energy storage devices for power plants.

[0129] Electrochemical devices, especially batteries such as the solid-state batteries described herein, can be used in, among others, motor vehicles, two-wheeled vehicles driven by electric motors, robots, aircraft (e.g. unmanned aerial vehicles such as drones), ships or stationary energy storage. Mobile devices such as vehicles, for example automobiles, bicycles, aircraft, or water vehicles such as boats or ships, are preferred. Other examples of mobile devices are those that are portable, such as computers, especially laptops, telephones, or power tools, for example from the construction sector, especially drills, battery-powered screwdrivers or battery-powered nailers.

[0130] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements of this application to the extent that any term may be unclear, this statement shall control. EXAMPLES

[0131] X-ray diffraction X-ray diffraction of the samples was collected on a Malvern Panalytical Aeris Research diffractometer (Cu, 600W, 40kV, 15mA, Soller slits 0.02°). Diffraction was collected over a 2 hour period in the range 10°-90°. Lattice parameters were determined by fitting the diffraction profile using the Full-Prof Suite. Profile fitting was performed using the F-43M space group of argyrodite.

[0132] Conductivity and electrochemical impedance spectroscopy (EIS) For impedance spectroscopy, the powder was sandwiched between two undried carbon paper electrodes (Papyex soft graphite, 0.2 mm thick, Mersen) and cold pressed at 500 MPa into a 6 mm die (uniaxial manual press MS15-MDD, Eurolab). The resulting pellet was then loaded into an airtight measurement cell (EQ-PSC, MTI). All measurements were performed under a pressure of 40 MPa.

[0133] AC impedance spectra were collected using a Biologic VMP3, and the temperature of the sample was controlled by a binder thermostatic bath. The cell was connected to a galvanostat-potentiostat, and a 20 mV sinusoidal perturbation was applied near the OCV from 1 MHz to 10 kHz, and the PEIS spectrum was recorded. 25 points per decade were recorded, and each point was averaged from 50 measurements. A model circuit was used to fit the curve and extract the ionic resistance. Temperature tests were performed in 2-hour steps at each temperature, and a spectrum was recorded at the end. The temperature was set from -20°C to 60°C, and then returned to 30°C.

[0134] The electronic conductivity is measured by direct current measurements at 2 volts and is determined after 1 hour by the asymptotic method.

[0135] EIS measurements show that the LiPSMgX solid material according to the present invention has improved ionic conductivity and lower activation energy compared to the conductivity and activation energy of the LiPSMgX material according to the prior art.

[0136] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements in this application to the extent that any term may be unclear, the statements herein shall control.

[0137] example Comparative Example 1: Synthesis of Li6PS5Cl In an Ar-filled glove box, Li2S (Lorad Chemical), LiCl (Sigma-Aldrich) and P2S5 (Sigma-Aldrich) were weighed and mixed in stoichiometric proportions to obtain 4 g of the desired composition Li6Na5PS5Cl. The mixture was then transferred to a 45 mL ZrO2 jar filled with 5 mm zirconia (YSZ) balls. The ball-to-powder ratio was fixed at 16.5. The jar was sealed, removed from the glove box and placed in a Fritsch Planetary Micro Mill Pulverisette 7. The mixture was ball milled for 2 h at a rotation speed of 500 RPM with a 15 min break every 30 min of milling. The powder was collected in an Ar-filled glove box (<1 ppm H2O, <1 ppm O2). The resulting powder was transferred to a sealed SiC crucible. The crucible was heated to 500 °C in a tube furnace under N2 atmosphere at a heating rate of 5 °C / min and kept at this temperature for 12 h. The sample was then cooled to room temperature. It was retrieved in an Ar-filled glove box and crushed in a mortar. The argyrodite phase was identified and was phase pure with a lattice parameter of 9.8519 Å. The ionic conductivity at 30 °C was 3.2 mS / cm, associated with an activation energy of 0.38 eV. The electrical conductivity at 30 °C was 4 × 10 -9 It was S / cm.

[0138] Comparative example 2: Li 5.25 Mg 0.25 P.S. 4.75 Cl 1.25 Synthesis of In an Ar-filled glove box, Li2S (Lorad Chemical), LiCl (Sigma-Aldrich), MgCl2 (Sigma-Aldrich), and P2S5 (Sigma-Aldrich) were weighed and mixed in stoichiometric proportions to produce 4 g of Li2S of the desired composition. 5.25 Mg 0.25 P.S. 4.75 Cl 1.25The mixture was then transferred into a 45 mL ZrO2 jar filled with 5 mm zirconia (YSZ) balls. The ball to powder ratio was fixed at 16.5. The jar was sealed, removed from the glove box, and placed in a Fritsch Planetary Micro Mill Pulverisette 7. The mixture was ball milled for 2 hours at a rotation speed of 500 RPM with a 15 minute break every 30 minutes of milling. The powder was collected in an Ar filled glove box (<1 ppm H2O, <1 ppm O2). The resulting powder was transferred into a sealed SiC crucible.

[0139] The crucible was heated to 500 °C in a tube furnace under N2 atmosphere at a heating rate of 5 °C / min and kept at this temperature for 12 h. The sample was then cooled to room temperature. It was retrieved in an Ar-filled glove box and crushed in a mortar. The argyrodite phase was identified and was quasi-phase pure. Some traces of MgS were also observed. The lattice parameter of argyrodite was 9.8188 Å. The ionic conductivity at 30 °C was 2.6 mS / cm, associated with an activation energy of 0.38 eV. The electrical conductivity at 30 °C was 2 × 10 -9 It was S / cm.

[0140] Comparative example 3: Li 5,8 Mg 0.1 Synthesis of PS5Cl Comparative Example 3 was carried out in the same manner as Comparative Example 2, in a suitable ratio, to obtain 4 g of Li of the desired composition. 5,8 Mg 0.1 PS5Cl was obtained. The argyrodite phase was identified with a lattice parameter of 9.8457 Å, which was phase pure. The ionic conductivity at 30 °C was 1.6 mS / cm, associated with an activation energy of 0.38 eV. The electrical conductivity at 30 °C was 3.10 -9 It was S / cm.

[0141] Example 1: Li 5.375 Mg 0.125 P.S. 4.625 Cl 1.375 Synthesis of By carrying out Example 1 as well as Comparative Example 2 in the appropriate proportions, 4 g of Li of the desired composition was obtained. 5.375 Mg 0.125 P.S. 4.625 Cl 1.375 The argyrodite phase was identified with a lattice parameter of 9.8131 Å, which was phase pure. The ionic conductivity at 30 °C was 5.4 mS / cm, associated with an activation energy of 0.38 eV. The electrical conductivity at 30 °C was 1 × 10 -8 It was S / cm.

[0142] Example 2: Li 5,375 Mg 0,0625 P.S. 4.5 Cl 1.5 Synthesis of By carrying out Example 2 in the same manner as Comparative Example 2 in the appropriate proportions, 4 g of Li of the desired composition was obtained. 5,375 Mg 0.0625 P.S. 4.5 Cl 1.5 The argyrodite phase was identified and was phase pure with a lattice parameter of 9.8067 Å. The ionic conductivity at 30 °C was 5.8 mS / cm, associated with an activation energy of 0.36 eV. The electrical conductivity at 30 °C was 4.10 -9 It was S / cm.

[0143] As is apparent from the examples, the composition range of the present invention, i.e., the range defined by 0.01≦x≦0.35 and 1.3≦y≦1.6, is represented by the general formula Li 7-2x-y Mg x P.S. 6-y X y The solid material according to (I) has very high ionic conductivity and low activation energy, as well as low electronic conductivity.

[0144] The comparative examples show that, despite the fact that a pure argyrodite phase is obtained outside the compositional range according to the invention, the resulting solid material has a much lower ionic conductivity.

Claims

1. The following general formula (I): Li 7-2x-y Mg x PS 6-y X y (I) (In the formula, X is a halogen selected from the group consisting of F, Cl, I, and Br, or combinations thereof; x is a number such as 0.01≦x≦0.35, y is a number such as 1.3≦y≦1.6) of solid material.

2. 2. The solid material of claim 1, wherein X is Cl.

3. 0.01≦x≦0.25, 1.3≦y≦1.5, 3. The solid material according to claim 1 or 2.

4. The following formula: Li 5.375 Mg 0.125 P.S. 4.625 C 1.375 Li 5,375 Mg 0,0625 P.S. 4.5 C 1.5 The solid material according to any one of claims 1 to 3,

5. 5. A solid state material according to any one of claims 1 to 4, having an ionic conductivity of at least 3.3 mS / cm measured on a pressed (500 MPa) pellet by impedance spectroscopy.

6. The particle size distribution measured by laser diffraction in p-xylene was: d50 value of less than 50 μm; a d10 value of more than 0.05 μm, and / or d90 value of less than 100 μm The solid material according to any one of claims 1 to 5, which is in the form of a powder having a particle size distribution exhibiting:

7. A process for producing a solid material according to any one of claims 1 to 6, comprising the steps of: a) combining ingredients, optionally in one or more solvents, to obtain a composition; b) optionally subjecting the composition obtained in step a) to a mechanical treatment; c) optionally removing at least a portion of the one or more solvents from the composition obtained in step b) to obtain a solid residue; d) optionally pressing the solid residue from step c) into pellets; e) heating the residue obtained in step c), for example in the form of pellets, under an inert atmosphere at a temperature in the range of 350° C. to 580° C. for a time in the range of 1 hour to 12 hours, thereby forming the solid material; f) optionally processing the solid material obtained in step e) to a desired particle size distribution; A process including.

8. 8. The process according to claim 7, wherein in step b), the mechanical treatment is carried out by wet milling or dry milling.

9. A process for producing a solid material according to any one of claims 1 to 6, comprising the steps of: a') mixing the raw material with one or more solvents to obtain a solution; b') removing at least a portion of the one or more solvents from the composition obtained in step a') to obtain a solid residue; c') optionally pressing the solid residue from step b') into pellets; d') optionally heating the residue obtained in step b'), for example in the form of pellets, under an inert atmosphere at a temperature in the range of 350°C to 580°C for a time in the range of 1 hour to 12 hours, thereby forming a solid material; e') optionally processing the solid material obtained in step d') to a desired particle size distribution; A process including.

10. The raw material is at least lithium sulfide (Li 2 S), phosphorus sulfide (P 2 S 5 ), lithium chloride (LiCl), as well as magnesium sulfide (MgS), magnesium chloride (MgCl 2 10. The process according to any one of claims 7 to 9, wherein the magnesium compound is selected from the group consisting of magnesium phosphate, magnesium phosphate phosphate, magnesium phosphate phosphate salts, magnesium phosphate ...

11. A solid material obtainable by the process according to any one of claims 7 to 10.

12. Use of the solid material according to any one of claims 1 to 6 as a solid electrolyte.

13. A solid electrolyte comprising at least the solid material according to any one of claims 1 to 6.

14. at least A metal substrate; At least one layer directly adhered to the metal substrate, (i) a solid material according to any one of claims 1 to 6, (ii) at least one electroactive compound (EAC); (iii) optionally at least one lithium ion conducting material (LiCM) other than the solid material of the present invention; (iv) optionally, at least one electrically conductive material (ECM); (v) optionally a lithium salt (LIS), and (vi) optionally at least one layer made from a composition comprising at least one polymeric binding material (P); An electrode comprising:

15. at least A solid material according to claims 1 to 6, Optionally at least one polymeric binder material (P), Optionally at least one metal salt, in particular a lithium salt, Optionally at least one plasticizer; Contains the separator.

Citation Information

Cited By

  • Method for producing an acid fluoride-based solid electrolyte and a method for producing an all-solid-state lithium-ion battery

    JP2026164637A

  • Oxyfluoride-based solid electrolyte production method and all-solid-state lithium ion battery production method

    WO2026203565A1